2015
DOI: 10.24966/imph-2493/100001
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Apatite-Based Functional Nanoparticles as Promising Newcomers in Nanomedicine: Overview of 10 Years of Initiatory Research

Abstract: Biomimetic calcium phosphate apatites, analogous to bone mineral, may now be produced synthetically. Their intrinsic biocompatibility and the nanometer dimensions of their constitutive crystals not only allow one to envision applications in bone tissue regeneration, but also in other medical fields such as nanomedicine, and in particular in view of cell diagnosis.In this mini-review, we look back at 10 years of our dedicated research, and summarize the main advances made in terms of preparation, physical-chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…It is possible to prepare biomimetic analogs to bone apatite, either carbonate-substituted or non-carbonated, by soft chemistry using close-to-physiological synthesis routes such as coprecipitation (Delgado-Lopez et al 2012;Iafisco et al 2011Iafisco et al , 2012Vandecandelaere et al 2012;Pasteris et al 2012). These synthetic compounds not only help us to understand biomineralization phenomena, but also encourage the development of bio-inspired materials for bone regeneration and, more recently, in nanomedicine, e.g., for oncology (Drouet et al 2015;Kramer et al 2014;Iafisco et al 2012Iafisco et al , 2013Bouladjine et al 2009), gene delivery (Hossain et al 2010;Sokolova et al 2006;Chowdhury and Akaike 2005) and hematology (Stefanic et al 2017). For such applications, raw precipitates must be processed into either 3D scaffolds, 2D surface coatings on appropriate substrates, or even 1D individualized nanoparticles; this processing step may lead to non-negligible modifications of the initial nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to prepare biomimetic analogs to bone apatite, either carbonate-substituted or non-carbonated, by soft chemistry using close-to-physiological synthesis routes such as coprecipitation (Delgado-Lopez et al 2012;Iafisco et al 2011Iafisco et al , 2012Vandecandelaere et al 2012;Pasteris et al 2012). These synthetic compounds not only help us to understand biomineralization phenomena, but also encourage the development of bio-inspired materials for bone regeneration and, more recently, in nanomedicine, e.g., for oncology (Drouet et al 2015;Kramer et al 2014;Iafisco et al 2012Iafisco et al , 2013Bouladjine et al 2009), gene delivery (Hossain et al 2010;Sokolova et al 2006;Chowdhury and Akaike 2005) and hematology (Stefanic et al 2017). For such applications, raw precipitates must be processed into either 3D scaffolds, 2D surface coatings on appropriate substrates, or even 1D individualized nanoparticles; this processing step may lead to non-negligible modifications of the initial nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that apatite nanoparticles could be formulated as colloidal suspensions via the formation of an external organic corona surrounding the particles. 2 aminoethylphosphate (AEP) as well as phosphonated polyethyleneglycol have been shown to be efficient stabilizing agents to form individualized colloidal apatite NP [23,28]. In the case of AEP stabilized apatite NP, positively charged particles are obtained due to the presence of an amino group on the AEP molecule; however the addition of hex ametaphosphate (HMP) anions was found to improve significantly the dispersibility of the particles, facilitate their purification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for appropriate and potentially multifunc tional systems for nanomedicine, bio-inspired systems appear particularly appealing due to their expectedly high intrinsic bio compatibility. In this context, apatite-based systems-approaching the minerai part of bones -represent in particular a promising type of biocompatible systems; and previous works have shown the possibility to obtain colloidal-like formulations of apatite nanopar ticles through surface engineering [1,[20][21][22][23]. Apatite-based NPs may thus be considered as promising potential candidates for use in nanomedicine.…”
mentioning
confidence: 99%
“…To be envisioned for use in the human body, this corona should also be composed of biocompatible constituting molecules. In our approach initiated several years ago [1,22,29], this stabilization is for example realized by surface grafting of either a phospholipid moiety (2-aminoethylphosphate, or AEP, representing hydrophilic head of the phospholipid phosphatidylethanolamine, a component of cell membranes) [30] or a phosphonate-terminated polyethyleneglycol (denoted (PEG)P). Obtained stabilized apatite colloidal nanoparticles, involving a biomimetic apatite phase close to bone mineral (nonstoichiometric apatite with surface active sites) [31] and stabilized with AEP, were for example shown to exhibit high cytocompatibility towards different types of cells (mesenchymal stem cells form adipose tissue, breast cancer cells), and no pro-inflammatory potential was detected when these NPs were contacted with human monocytes/macrophages [6].…”
mentioning
confidence: 99%